PENGARUH MODEL PEMBELAJARAN LEARNING CYCLE 5E DISERTAI MIND MAP TERHADAP HASIL BELAJAR IPA BIOLOGI SISWA KELAS VIII SMP NEGERI 5 KARANGANYAR TAHUN PELAJARAN 2015/2016 - Hargiono Hargiono; Maridi Maridi; Bowo Sugiharto (BIO-PEDAGOGI, 2016)
The purpose of this research is to ascertain the influence of learning cycle 5E models accompanied mind map toward biology learning achievment of VIII grade students at SMP Negeri 5 Karanganyar academic year 2015/2016. This research was quasi experiment research which used posttest only nonequivalent control group design. This research applied learning cycle 5E learning models accompanied mind map in experimental group and direct instruction learning models in control group.  The population of this research was all of VIII grade students at SMP Negeri 5 Karanganyar in academic year 2015/2016.   Sampling techniques used cluster sampling that choosed VIII A, VIII B, and VIII G as experiment group, and VIII H as control group. Data was collected using multiple choice test, observation sheet, and document.  The hypotheses analyzed by anova test. Result of data analysis using one way anova showed that  experiment group with application of learning cycle 5E learning models accompanied mind map has different signification 0.000 with other  experiment groups and Fstatisticwith value 7,436 is higher than F(α,df)with value 2,440.This research concluded that application of learning cycle 5E learning models accompanied mind map has real influential toward student’s biology learning achievement of VIII grade students at SMP Negeri 5 Karanganyar especially cognitive domain. Keywords : learning cycle 5E, mind map,learning achievment.